Study of the Theory and Practice of Educational Supervision in Islamic Education in Indonesia - Aries Musnandar; Sutrisno Sutrisno; Muhammad Talhah Ajmain@Jimaain; Galuh Prabowo; Nyak Dara Najmatus Subhi (Lingeduca: Journal of Language and Education Studies, 2024)
This study examines the extent to which the concepts, theories, and practices of educational supervision can be developed in a pluralistic society, particularly in the context of Indonesian education. Educational supervision in this context refers to instructional supervision, which is more focused on supporting and facilitating teachers to enhance the quality of instruction in achieving specific goals according to the concept of educational supervision. In Indonesia, the theory and practice of educational supervision face various challenges, given that general education is also conducted by religious-based educational institutions, particularly Islam, which oversees numerous Islamic schools, madrasahs, and pesantren. This study employs a qualitative method with a library research approach that critiques the implementation of the concepts, theories, and practices of educational science, particularly related to instructional or teaching supervision. The findings indicate that educational supervision in Islamic educational institutions has not yet been effective and efficient, as there remains a gap between the ideal and the reality in the field. Educational theories and the legal aspects of education enshrined in education laws have not been fully implemented properly. The study concludes that the education system must first emphasize the implementation of educational processes such as improving and equalizing the quality of teachers, enhancing learning facilities, libraries, and laboratories. A paradigm shift is necessary, changing the focus from solely academic (hard skills) to also include soft skills and non-academic aspects. The teaching and learning process should be designed to be more engaging, focusing on the improvement of the affective (attitudes) and psychomotor (skills) domains, rather than being limited to the cognitive (knowledge) domain alone.